Alabaster sculpture in Europe (1300-1650). - Debaene, Marjan; Jugie, Sophie; Zöschg, Michaela; Tentoonstelling. Leuven. M Leuven (Turnhout : Harvey Miller / Brepols, 2022)
Alabaster was a popular material in European sculpture, especially from the fourteenth to the seventeenth century. Its relative availability and easy to sculpt characteristic made it a highly suitable material for both large monuments and small objects, for mass production and individual works, from England to Spain and France to the Netherlands, Germany and Poland. This material has been the subject of multidisciplinary research in various European countries for several decades. The research combines material analyses with historical and art-historical approaches. This publication, made for the occasion of the large exhibition on the theme at M Leuven opening on October 14th, brings together all renown specialists on the material and sheds light on the many facets of alabaster, such as its physical and chemical properties as well as its translucency, its whiteness, its softness, and its beautiful sheen, all of which made it a popular material used in different types of sculpture from the middle ages to the baroque, all throughout Europe, ranging from bespoke tombs, funerary monuments and commissioned sculptures and altarpieces to commercially interesting formulas such as English or Mechelen alabaster reliefs. 00Exhibition: M Leuven, Belgium (14.10.2022-26.2.2023).
14.10.2022 - 26.02.2023
boek
Keywords: Exhibitions